Spillovers from legal cooperation to non-competitive prices - Jeroen Hinloopen; Stephen Martin; Sander Onderstal; Leonard Treuren (Tinbergen Institute, 2024)
Antitrust laws prohibit private firms to coordinate their market behavior, yet many types of interfirm cooperation are legal. Using laboratory experiments, we study spillovers from legal cooperation in one market to non-competitive prices in a different market. Our theoretical framework predicts that such cooperation spillovers are most likely to occur for intermediate levels of competition. Our experimental findings support this theoretical prediction. In addition, our experimental results show that repeated interaction and communication about prices in a market are not necessary to achieve non-competitive prices in that market, as long as subjects can form binding agreements in a different market. Results from additional treatments suggest that commitment and multimarket contact are necessary for cooperation spillovers to emerge.
Keywords: C9; D43; L13; L41; 330; Cartel; Communication; Cooperation spillovers; Antitrust; Experiment